Hodgkin lymphoma and Ewing sarcoma in pediatric patient carrying germline PALB2 variant: a case report and literature review - Czarny, Jakub; Galli, Dominika; Wziątek, Agnieszka; Pastorczak, Agata; Szmyd, Bartosz; Przybyszewski, Borys; Raciborska, Anna; Jończyk-Potoczna, Katarzyna; Derwich, Katarzyna (Frontiers in Oncology, 2025)
Germinal predisposition to malignancy is found in approximately 10% of oncological pediatric patients. As awareness of cancer risk factors associated with germline mutations increases, and with advancements in molecular techniques, more carefully selected patients are being tested. This approach enables the identification of new variants—both those that are clearly linked to tumorigenesis and candidates, which biological role needs to be functionally verified. Pathogenic variants within cancer-predisposing genes not only increase nearly eightfold the risk of secondary cancers but also may be associated with excessive toxicity of antineoplastic treatment. We present the case of a girl who developed classical Hodgkin lymphoma at the age of 8 years and secondary Ewing sarcoma at the age of 16 years. Her father was diagnosed with classical Hodgkin lymphoma at the age of 27 years. Genetic testing revealed the carriership of a germline heterozygous variant in the PALB2 gene (NM_024675.4:c.110G>A, p.Arg37His) in both the patient and her father. Since the patient was exposed to chemotherapy due to lymphoma prior to the development of secondary malignancy and the variant is classified as an aberration of unknown significance, the causative role of the PALB2 variant remains uncertain. Nevertheless, the presented case may indicate the possible interplay between inherited genetic predisposition and the exposure to cytostatic drugs, which both are involved in promoting secondary cancers in pediatric patients.